2009
DOI: 10.1002/sia.3045
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐thin SiO2 on Si IX: absolute measurements of the amount of silicon oxide as a thickness of SiO2 on Si

Abstract: Results from a study conducted between National Metrology Institutes (NMIs) for the measurements of the absolute thicknesses of ultra-thin layers of SiO 2 on Si are reported. These results are from a key comparison and associated pilot study under the auspices of the Consultative Committee for Amount of Substance. 'Amount of substance' may be expressed in many ways, and here the measurand is the thickness of the silicon oxide layers with nominal thicknesses in the range 1.5-8 nm on Si substrates, expressed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 23 publications
(30 reference statements)
2
42
0
Order By: Relevance
“…Key comparison reference value and their associated uncertainties were determined from the weighted means and the expanded weighted standard deviations of the means. [7] The standard uncertainty in the measurement of thickness of nm silicon oxide films can be described by the following equation.…”
Section: Key Comparison For Thickness Measurement Of Sio 2 Films On Smentioning
confidence: 99%
See 2 more Smart Citations
“…Key comparison reference value and their associated uncertainties were determined from the weighted means and the expanded weighted standard deviations of the means. [7] The standard uncertainty in the measurement of thickness of nm silicon oxide films can be described by the following equation.…”
Section: Key Comparison For Thickness Measurement Of Sio 2 Films On Smentioning
confidence: 99%
“…4, 8 nm. [7] u F : different peak shape algorithms u L : electron attenuation length u n and u θ have random contributions (type A) and the other terms largely involve systematic contributions (type B). u E is less than 0.025 nm and u A is negligible for an analyser with small cone entrance angle.…”
Section: Uncertainty In the Thickness Measurement By Xpsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both L and R o may be calibrated using reference samples and then d may be determined with significantly greater accuracy. [1,3] In this case, the accuracy of the angle of emission becomes the factor that limits the accuracy in determining d. [4] In the machining of these sophisticated spectrometers, one would expect the angles to have an accuracy of better than 0.5…”
Section: Introductionmentioning
confidence: 98%
“…A comparison of the thickness determination of SiO 2 films (2–10 nm) on Si substrates was conducted using CCQM‐K32, P84, and P38 . The results revealed that there was an offset in the reported thickness values among the measurement methods.…”
Section: Introductionmentioning
confidence: 99%